Reachability-based diagnosability for hybrid systems - Vieira, Jéssica dos Santos (2021)
Submitted by Paloma Arruda (palomaoliiveira75@gmail.com) on 2021-02-20T04:23:12Z No. of bitstreams: 1 JessicaDosSantosVieira.pdf: 1680322 bytes, checksum: 3e2ca5de31e30315af094878547a2962 (MD5)